2007
DOI: 10.1590/s0066-782x2007000500021
|View full text |Cite
|
Sign up to set email alerts
|

Revascularização do miocárdio em paciente com situs inversus totalis

Abstract: Pego-Fernandes et al Myocardial revascularization in a patient with situs inversus totalisArq Bras Cardiol 2007; 88(5) : e100-e103 , but despite the fact this is not the first Brazilian report, it can be considered the most complex procedure to date, considering the number of anastomoses performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Only 14 years later, Rosa et al [ 2 ] , in 2002, reported the second case in the country, performing a triple-vessel revascularization with CPB utilizing RIMA and two saphenous vein grafts. Pego-Fernandes et al [ 3 ] reported a case in which they performed an on-pump quintuple coronary artery bypass grafting and Saadi et al. [ 4 ] reported another case in which they performed a triple on-pump coronary bypass grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Only 14 years later, Rosa et al [ 2 ] , in 2002, reported the second case in the country, performing a triple-vessel revascularization with CPB utilizing RIMA and two saphenous vein grafts. Pego-Fernandes et al [ 3 ] reported a case in which they performed an on-pump quintuple coronary artery bypass grafting and Saadi et al. [ 4 ] reported another case in which they performed a triple on-pump coronary bypass grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Through simple anatomical observation, it can be determined that there was no change in the heart position after the corpse underwent fixation. This case is characterized as a dextrocardia case, as the heart apex was completely turned to the right antimere [2][3][4][5]7,9 . It cannot be classified as a dextroversion case, as in the latter, the heart is located in the right hemithorax with the apex turned to the left antimere, different from what was observed in the present case 5,9 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Dextrocardia is an embryologic malformation characterized by the displacement of the largest axis (base to apex) of the heart to the right side of the chest, with reversion of the apical inclination. This malformation is caused by an anomalous rotation of the primitive heart tube to the left, in which the bulboventricular loop bends to the left, in a specular image of the normal condition, which occurs around the 8 th week of embryonic life 1,2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than 10 cases have been reported worldwide in patients who have undergone coronary artery bypass grafting with this condition. This is the third case in Brazil [4][5][6]. Less frequent is the use of the right internal thoracic artery.…”
Section: Discussionmentioning
confidence: 99%